Pengaruh Latihan Small Side Game Terhadap Akurasi Passing Futsal di Ekstrakurikuler SMPN 5 Cianjur : (Penelitian Free Eksperimen di Smpn 5 Cianjur) - Arief Adhitia Hamzah; Ai Faridah; Acep Ruswan; Dian Permana; Bela Santika; Muhamad Algifari Mu'minin (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
The focus of this research is the low passing accuracy skills of students in futsal games. The purpose of this study was to determine "The Effect of Small Side Game Training on Passing Accuracy in futsal games". The research method used is the experimental method and this research instrument uses a passing accuracy test. The population in this study were SMPN 5 Cianjur futsal players totaling 40 people, using random sampling techniques and a sample of 20 people. Based on the results of data processing with statistical tests using the N-Gain score test, the Mean value is 0.6927 <0.7. Then it is included in the moderate category which means that the effectiveness of the increase is moderate. Then for the n-gain percent obtained the Mean value is 69.2738. So for this category it is between the 56-75 category which has a fairly effective interpretation in percentage form. Based on the results of these data, it is concluded that the effect of Small Side Game Training is quite effective on Futsal Passing Accuracy at SMPN 5 Cianjur Extracurricular.